A high-sensitivity 135GHz millimeter-wave imager by compact split-ring-resonator in 65-nm CMOS - Li, Nan (2015)
A high-sensitivity 135 GHz millimeter-wave imager is demonstrated in 65 nm CMOS by on-chip metamaterial resonator: a differential transmission-line (T-line) loaded with split-ring-resonator (DTL-SRR). Due to sharp stop-band introduced by the metamaterial load, high-Q oscillatory amplification can be achieved with high sensitivity when utilizing DTL-SRR as quench-controlled oscillator to provide regenerative detection. The developed 135 GHz mm-wave imager pixel has a compact core chip area of 0.0085 mm2 with measured power consumption of 6.2 mW, sensitivity of −76.8 dBm, noise figure of 9.7 dB, and noise equivalent power of 0.9 fW/√(Hz) Hz. Millimeter-wave images has been demonstrated with millimeter-wave imager integrated with antenna array.